2015
DOI: 10.1142/s0218271815420158
|View full text |Cite
|
Sign up to set email alerts
|

Black hole entropy and the zeroth law of thermodynamics

Abstract: By mapping the nonadditive entropy composition law of the Bekenstein-Hawking formula to an additive one via the so-called "formal logarithm" operation, a new approach to the black hole entropy problem is considered. The new temperature function satisfies the zeroth law of thermodynamics, and turns out to be independent of the mass-energy parameter of the black hole in the case of the Schwarzschild solution. It is shown that pure isolated black holes are thermodynamically stable against spherically symmetric pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 32 publications
(27 reference statements)
5
22
0
Order By: Relevance
“…These results are consistent with what we had previously found in studying the Schwarzschild solution by using the same approach [17].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…These results are consistent with what we had previously found in studying the Schwarzschild solution by using the same approach [17].…”
Section: Discussionsupporting
confidence: 93%
“…Indeed, we started with the question of the nonextensivity/nonadditivity of the standard black hole entropy function, but we have not yet discussed whether it can satisfy the equilibrium compatibility condition of Abe's formula. In a recent paper [17], we investigated the thermodynamic and stability problem of a Schwarzschild black hole by considering the nonadditive entropy composition rule that is emerging from the Bekenstein-Hawking description. We showed that in this case the entropy composition rule of the Schwarzschild problem takes the form…”
Section: A Nonparametric Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…The corresponding thermodynamic and stability problems (by also applying the formal logarithm method) has been studied in [72] and [73], respectively.…”
Section: Discussionmentioning
confidence: 99%
“…. , n. As we noted before, H α and R α are optimized by the same maximum entropy distribution (27) algthough the generalized coldness β L α depends on h and is related to β L α in accordance to equation (32). Thus, ME distribution can be represented in the form…”
Section: On the Equivalence Between Four Versions Of Generalized Thermentioning
confidence: 99%